CORRECTION OF PRONUNCIATION IN CHILDREN WITH HEARING IMPAIRMENTS THROUGH DACTYL EXERCISES: A MULTIMODAL SENSORIMOTOR APPROACH (International journal of artificial intelligence, 2026)
The article presents the results of an experimental study on the effectiveness of a system of dactyl (fingerspelling) exercises in correcting pronunciation disorders in school-aged children with hearing impairments. The theoretical-methodological foundations of the multimodal sensorimotor approach are revealed; a four-stage correctional-developmental program based on the integration of finger motor activity and articulatory praxis is described. The experimental work was carried out at the Almazor district School No. 106 for deaf and hard-of-hearing children (Tashkent, Uzbekistan) with the participation of 64 fifth-grade pupils. A statistically significant improvement in the pronunciation skills of the experimental group was established according to the criteria of phonetic accuracy, speech intelligibility, articulatory mobility, and rhythmic-melodic organization (χ² = 17.86 at p<0.01). The findings confirm the necessity of integrating dactyl exercises as a central component of correctional-logopedic work in the system of special education.